Determination of Risk Factors for Pre-eclampsia in a Tertiary Hospital of Bangladesh: A Descriptive Study - Ghani, Afroza; Ila, Israt Jahan; Tasmin, Khandaker Shehneela; Zakaria, Rooh E; Ferdows, Jannat Ara; Sultana, Nasrin (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Pre-eclampsia (PE), a hypertensive disorder of pregnancy is estimated to complicate 2%-8% of pregnancies and remains a principal cause of maternal and fetal morbidity and mortality. The identification of its predisposing factors in the pre-pregnancy and initial stage of pregnancy will help in reducing the morbidity and mortality. Aim: The aim of this study is to determine the risk factors for PE among pregnant women in a tertiary level hospital. Methods: This study was conducted in the Department of Obstetrics and Gynaecology of Shaheed Suhrawardy Medical College & Hospital, a tertiary care hospital in Dhaka, Bangladesh, from January to December 2019. A total number of 50 pregnant women with pre-eclampsia, who got admitted in this hospital were selected as study group. This was a hospital based descriptive study. Results: Most of the participants were within 35-45 years of age group and mean age 38.92 ± 2.21. The factors that were found to be significant predictors of risk for development of PE were primigravida, inadequate education, low socio-economic status, past history of PE or hypertension and family history of PE or hypertension. J Shaheed Suhrawardy Med Coll 2021; 13(1): 3-7